2010
DOI: 10.1002/jbm.a.32909
|View full text |Cite
|
Sign up to set email alerts
|

Toward biomimetic materials in bone regeneration: Functional behavior of mesenchymal stem cells on a broad spectrum of extracellular matrix components

Abstract: Bone defect treatments can be augmented by mesenchymal stem cell (MSC) based therapies. MSC interaction with the extracellular matrix (ECM) of the surrounding tissue regulates their functional behavior. Understanding of these specific regulatory mechanisms is essential for the therapeutic stimulation of MSC in vivo. However, these interactions are presently only partially understood. This study examined in parallel, for the first time, the effects on the functional behavior of MSCs of 13 ECM components from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 66 publications
5
61
1
Order By: Relevance
“…Ode and colleagues have provided an excellent profile of human MSC integrin expression and a morphological characterization of the functional behavior of MSC on various ECM proteins. 26 A similar integrin expression profile of rhesus MSC as well as integrin inhibition studies may provide clues as to the preferential interactions of MSC with the parenchymal and vascular ECM, which may help tailor tissue-engineering approaches using these cells. 26,38 An important consideration toward the applicability of stem cells in lung regeneration is their ability to differentiate along pulmonary lineages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ode and colleagues have provided an excellent profile of human MSC integrin expression and a morphological characterization of the functional behavior of MSC on various ECM proteins. 26 A similar integrin expression profile of rhesus MSC as well as integrin inhibition studies may provide clues as to the preferential interactions of MSC with the parenchymal and vascular ECM, which may help tailor tissue-engineering approaches using these cells. 26,38 An important consideration toward the applicability of stem cells in lung regeneration is their ability to differentiate along pulmonary lineages.…”
Section: Discussionmentioning
confidence: 99%
“…26 A similar integrin expression profile of rhesus MSC as well as integrin inhibition studies may provide clues as to the preferential interactions of MSC with the parenchymal and vascular ECM, which may help tailor tissue-engineering approaches using these cells. 26,38 An important consideration toward the applicability of stem cells in lung regeneration is their ability to differentiate along pulmonary lineages. ESC can differentiate into a multitude of cell lineages, including respiratory epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that the ECM contributes to the functional behavior of MSCs and may be essential in guiding cell fate during tissuespecific differentiation. [42][43][44][45][46][47] Our group has recently demonstrated that bone marrow-and adipose-derived MSCs adhere to and proliferate within decellularized lung scaffolds in a rhesus macaque model of lung tissue engineering. 13 Here, the initial interaction of adipose-derived MSCs with decellularized scaffolds generated from MCT-PHT rat lungs is described in an effort to provide the necessary proof-of-principle that bioartificial organs can be derived from diseased sources.…”
mentioning
confidence: 99%